The bloodless princes - Bond, Charlotte (Bond, Charlotte. Fireborne blade, 2024)
"A tale of death, honor and true love's embrace. Come for the journey through the underworld. Stay for the minacious dragon-cat. It seemed the afterlife was bustling. Cursed by the previous High Mage, and following an...incident...with a supremely powerful dragon, newly-promoted High Mage Saralene visits the afterlife with a boon to beg of the Bloodless Princes who run the underworld. But Saralene and her most trusted advisor/champion/companion, Sir Maddileh, will soon discover that there's only so much research to be done by studying the old tales, though perhaps there's enough truth in them to make a start. Saralene will need more than just her wits to leave the underworld, alive. And Maddileh will need more than just her Fireborne Blade. A story of love and respect that endures beyond death. And of dragons, because we all love a dragon!"--